Locating science fiction - Milner, Andrew 1950- (Liverpool University Press, 2017)
Locating Science Fiction is a ground breaking and potentially paradigm-shifting book, a major intervention into contemporary theoretical debates about SF. Academic literary criticism has tended to locate SF primarily in relation to the older genre of utopia; fan criticism primarily in relation to fantasy and SF in other media, especially film and television; popular fiction studies primarily in relation to other contemporary genres such as the romance and the thriller. This bold new synthesis relocates SF in relation to each of these other genres and media and also to the historical and geographic contexts of its emergence and development. Locating Science Fiction effects a series of vital shifts in the way SF theory and criticism has conceptualised its subject, away from prescriptively abstract dialectics of cognition and estrangement and towards the empirically grounded understanding of what is actually a messy amalgam of texts, practices and artefacts. Inspired by Raymond Williams's cultural materialism, Pierre Bourdieu's sociology of culture and Franco Moretti's application of world systems theory to literary studies, Locating Science Fiction draws on the disciplinary competences of Comparative Literature, Cultural Studies, Critical Theory and Sociology to produce a powerfully persuasive mode of analysis, engagement and argument